Anak - Santos, Vilma; Barretto, Claudine; Torre, Joel; Quintos, Rory B.; Lee, Ricardo E. (Regal Home Video, 1999)
A domestic helper returns to the Philippines, where her 3 grown children reveal their resentment towards her. She's confused, as she had sacrificed to send money home. Her children, however, believe she had abandoned them. Life for everyone takes negative turns, and the mother is faced with a difficult choice: reclaim her family, or take the easy path and return to her old job.